ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PELAKSANAAN PELAPORAN PERTANGGUNGJAWABAN DANA GEREJA MASEHI INJILI DI MINAHASA (GMIM) KOTA MANADO - Kalangi, Melisa Mouren; Nangoi, Grace B.; Kalangi, Lintje (Universitas Sam Ratulangi, 2016)
The existence of problems that often occur in public sector organizations in this church organizations (GMIM) required him to prepare an accountability report. The obligation to prepare an accountability report of the church also refers to Law No. 14 of 2008 which is an Act to regulate on Public Information Openness (KIP). This study aims to identify and analyze whether Commitment, Human Resources, tools and motivation influential supporters Paporan Accountability Implementation Fund Evangelical Christian Church in Minahasa (GMIM) in the city of Manado, either simultaneously or partially. The method used is multiple linear regression analysis using the equation Y = Î± + Î²1X1 + Î²2X2 + Î²3X3 + Î²4X4 + Æ, Descriptive Statistics, Test Reliability and Validity, Classical Assumption Test, among others Normality Test Data, Test autocorrelation, Test Heteroskidastity, Test multikolinearitas. Hypothesis testing using the coefficient of determination, F test, t test. Based on F test showed a significance level of 0.006 is smaller than the statistical significance level of 0.05. This shows that H0 and H1 accepted. It can be concluded that jointly commitment variable (X1), the quality of human resources (X2), supporting devices (X3) and motivation (X4) effect on the reporting of an accountability of Evangelical Christian in Minahasa Church. While based on t-test significance level of commitment variable (X1), the quality of human resources (X2), a support device (X3), motivation (X4), among others, 0.212, 0.435, 0.083, 0.163 greater than the statistical significance level of 0.05. This shows that partially all variables does not affect the preparation of an accountability report of GMIM. Keywords: Accountability of funds, Public Sector Organizations.